Investigating the long-term impact of misinformation interventions in upper secondary education. - Thomas Nygren; Evgenia Efimova (PLoS ONE)
This study examines the long-term effects of educational interventions aimed at improving upper-secondary students' ability to identify and evaluate (mis)information. Using an experimental design with 459 students in authentic classroom settings, we tested three types of interventions: prebunking through the Bad News game, fact-checking skills via the News Evaluator workshop, and subject-specific disciplinary literacy interventions. Additionally, we investigated factors influencing students' abilities to identify credible and misleading news, including credibility importance, democratic ideals, actively open-minded thinking (AOT), self-rated fact-checking skills, and educational orientation. Neither the Bad News game nor the News Evaluator workshop significantly improved students' ability to evaluate credible and misleading news. Although students in the News Evaluator workshop slightly improved in evaluating a difficult-to-fact-check item, this effect was marginal. Furthermore, students did not report increased use of digital verification tools three months after the intervention, suggesting that isolated fact-checking instruction may be insufficient for fostering lasting behavioural change. The subject-specific interventions also failed to yield significant long-term effects. Students who rated access to credible information as important were better at identifying accurate news, while those who valued democracy were better at recognising false news. AOT was not associated with better discernment but increased scepticism toward both true and false news. Self-rated confidence in news evaluation did not predict actual performance, and students in vocational programs performed worse in identifying trustworthy news. While interventions promoting prebunking, fact-checking, and disciplinary literacy provide promising frameworks for misinformation education, their effects may diminish without sustained reinforcement. This study underscores the need for more embedded, repeated, and adaptive approaches that integrate retrieval practice, spaced learning, and digital tools to foster long-term engagement with credible information. Future research should explore how to enhance the impact of classroom-based misinformation education and investigate scalable strategies for reinforcing digital source evaluation skills over time.